Pengaruh struktur utang, ukuran perusahaan, dan profitabilitas terhadap kualitas laba - Veronica, Veronica; Syahzuni, Barlia Annis (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to analyze and determine the effect of debt structure, firm size and profitability on earnings quality. This study uses a quantitative method. The population of this research is food and beverage companies listed on the Indonesia Stock Exchange as many as 30 companies. Based on the purposive sampling technique, a sample of 20 companies was obtained with the criteria of food and beverage companies that generated positive profits during 2018-2021 so that the research sample obtained was 80 samples. The data in this study were taken through the official website of each company or through the official website of the Indonesia Stock Exchange (IDX). The analysis technique used in this research is multiple linear regression. The results of the study show that: (1) debt structure, firm size and profitability show a simultaneous effect on earnings quality, (2) debt structure has a negative effect on earnings quality, (3) firm size has a positive effect on earnings quality, and (4) Profitability has a positive effect on earnings quality in food and beverage sector companies listed on the Indonesia Stock Exchange in 2018-2021. Simultaneously DER, Ln Total Assets and NPM affect earnings quality in the food and beverage sector in 2018-2021.